2023
DOI: 10.1371/journal.pone.0279628
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and associated factors among adult cancer patients receiving cancer treatment at oncology unit in Amhara region, Ethiopia

Abstract: Introduction Fatigue is one of the most commonly and frequently reported symptoms by cancer patients. The cause of fatigue is multifactorial in origin, and its impact varies in range from affecting patients’ daily social life, and physical, mental, economic, and social well-being to becoming a threat to their quality of life. Therefore every cancer patient needs to be screened for fatigue and considered as one of the vital signs. Objective To assess the prevalence of fatigue and associated factors among adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In the same way, anemia is highly prevalent in Ethiopia (3,12). The prevalence ranges from 23% to 54.8% across different types of solid tumor (3,13), and the prevalence ranges from 21.7% in patients with breast cancer to 50.95% in patients with cervical cancer (12).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the same way, anemia is highly prevalent in Ethiopia (3,12). The prevalence ranges from 23% to 54.8% across different types of solid tumor (3,13), and the prevalence ranges from 21.7% in patients with breast cancer to 50.95% in patients with cervical cancer (12).…”
Section: Introductionmentioning
confidence: 96%
“…If untreated, anemia could have additive consequences to cancer patients. For example, untreated anemia may compromise the quality of life (QoL) and causes fatigue in cancer patients (22,24,25).For example, a cross-sectional study in Ethiopia confirmed that anemic cancer patients had increased risk of experiencing fatigue compared to patients without anemia (13). In addition, Clarke and Pallister (14)had reviewed that around 65% of cancer patients have an overall increased risk of death related to anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacological interventions can be considered a helpful approach, but evidence in this regard is limited and recommendations are often contradictory [ 19 21 ]. In fact, pharmacological strategies for the treatment of CRF have not yet been established, nor is there any consensus on pharmacological management [ 9 , 19 ]. As a result, more research on pharmacological treatments of CRF is needed, especially in patients with advanced cancer [ 20 ].…”
Section: Introductionmentioning
confidence: 99%